Effect of Experimental Parameters on the Formation of Hydrogels by Polyelectrolyte Complexation of Carboxymethylcellulose, Carboxymethyl Starch, and Alginic Acid with Chitosan - Elizabeth Henao Mejía; Héctor Contreras; Ezequiel Delgado; Germán Quintana (International Journal of Chemical Engineering)
Differences in morphology, pH, and electric charge of chitosan (CS) based hydrogels prepared by complexation with carboxymethylcellulose (CMC), carboxymethylated starch (CMS), and alginic acid (AA) at different polymers ratios and changing the order of addition were studied. CMC/CS and AA/CS hydrogels were amorphous and porous three-dimensional networks, with smaller pores at higher anionic polymer/CS ratios. Gelation time increased the agglomeration in the case of CMC/CS and CMS/CS gels. CMC/CS gels showed negative zeta potential values around −372 mV to −51 mV and CMS/CS gels in the range of −526 mV and −158 mV.